NILAI-NILAI ETIS ADAT PERKAWINAN MASYARAKAT ACEH (Ethical Values of Marriage Custum ofAceh Society ) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The title of this research is " Ethical Values of Marriage Custom of Aceh Society". The aims of this research is to study the philosophical-ethics mean¬ing in the marriage custom ceremony of Aceh society, to give critical evalua¬tion of philosophical-ethics of symbols in that ceremony, and to know is that ethical meaning be able to anticipate the foreign cultural influence which is incompatible generally with personality of Indonesian society and especially with society Aceh custom. This research is library research. Both primary and secondary data taken from some books, previous research result, and interview with custom, reli¬gion, and society figures, and reseacher that has competency in the field of marriage custom. Methodical stages in this research is data collecting, iden¬tify and classify of matter, and analyze by use metodical of philosopical-reflective-hermeneutics, with stages viz description, interpretation, heuris¬tic, and critical reflective. Description used to depict contents or matter and aims of marriage ceremony. Interpretation used to interpret symbols in that custom ceremony. Heuristic used to be able to open a new way in solving problems in that ceremony custom so that achieved a new understanding and meaning deeply. Critical reflection used to give reinterpretation of that analyze result to get a new comprehensively understanding of philosophi¬cal-ethics in the custom ceremony. The summary of this research is that symbols in the marriage custom ceremony of Aceh society represent the acculturation from both religion value and culture that have religius and ethics in their character. Religius because it depict of human being and God relation. Ethics because it depict of fellow being relation including having a good attitude to both parents, moral teaching to husband and wife or bride. Intend of ethical meaning that will be achieved in the custom ceremony is in order to every society members and especially bride be able to internalize morality values so that get a inner and outsider nappy life. Intend of ethics of the custom ceremony be able to be made a shield from the outside culture influence which is irrelevant with own personality.